Persiapan Siswa Kelas 6 dalam Menghadapi Ujian Akhir Sekolah di Sekolah Dasar Negeri (SDN) 14 Bebesen Aceh Tengah - Ahmad Yunus Mokoginta Harahap; Ainun Ainun; Rahmayati Rahmayati (Neolectura, 2022)
To measure the achievement of a learning competence, a measuring instrument is needed in the form of an evaluation of learning outcomes. There are several kinds of evaluations that can be used as measuring tools in an educational institution such as summative tests which aim to determine grade promotion, and school exams which aim to determine pass and fail. In an effort to prepare for school exams there are various ways that a student does. This study aims to describe the preparation of 6th grade students at SDN 14 Bebesen in facing school exams. This study uses qualitative research methods, data collection techniques using interviews and observations, data analysis techniques using three stages of analysis, namely data reduction, data presentation, and drawing conclusions. The results of the study found that grade 6 students at SDN 14 Bebesen were less likely to prepare for school exams by preparing materials, studying hard and even registering for additional lessons at guidance institutions, reducing playing time, although there were also students who did not prepare themselves carefully.